STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF WORDWALL - Irawan, Tata Regita Sherfaty; Wahyuni, Aelista Dwi; Tahrun (Universitas PGRI Palembang, 2025)
This study explores the impact of word walls in enhancing student learning motivation, addressing factors both internal and external to students. The purpose of this research is to examine student perceptions of the application of word walls. A qualitative approach was used, involving questionnaires and interviews as data collection instruments. The research respondents consisted of 33 tenth-grade students from SMA Negeri Plus Banyuasin III. The results indicate that word walls play a significant role in boosting student interest in learning, expanding vocabulary, and supporting the acquisition of new knowledge through reading books. Additionally, word walls contribute to the development of students' reading, writing, and speaking skills. Based on these findings, it is concluded that word walls are an effective tool for motivating students to engage in their learning process. It is recommended that educators consider incorporating word walls into their teaching strategies to improve student engagement and language development.